Students’ Gains in English as a Second or Foreign Language through Game-Based Learning: A Meta-Analysis - Barrun, Jason S.; Gilbas, Sherill A. (OKARA: Jurnal Bahasa dan Sastra, 2024)
Various digitally aided applications have prompted ESL/EFL teachers to adopt them in their classrooms for games and experiments; hence, the concept of play in pedagogical settings has grown and become more modern, modifying the structures of Game-based Learning (GBL). This study, therefore, aims to analyze the effectiveness of GBL through meta-analysis. Following the set of inclusion and exclusion criteria, 16 studies in East Asia, Middle East Asia, and South America conducted from 2018 to 2023 have qualified for this study with 14 studies on tertiary level (n=822); 1 on secondary (n=56); and 1 on primary (n=46). Studies were obtained from Google Scholar, OpenAlex, Scopus, and Crossref. Further, the researchers used Harzing’s Publish or Perish software to exhaust the search process. Sample size, mean, and standard deviation were analyzed using the Jamovi software version 2.4 to determine the effect sizes (Hedge's g) and the results of moderator analysis, forest plot, funnel plot, and Classic Fail-Safe N test. Findings have shown that GBL, as an approach to teaching English, had a significant and positive effect (ES=1.19) on students' achievement in different language domains. Educational levels and the type of game-based learning employed as moderators were also proven to be factors that may affect learning outcomes. Hence, more studies testing the subgroups mentioned above should be conducted to facilitate more comprehensive comparative educational research in the future.